Taming peer review: On rigor, authenticity and becoming - Waghid, Yusef (South African Journal of Higher Education, 2018)
This article revisits the art of peer reviewing and argues that the process should remain a rigorous scholarly activity. Instead of making claims about what peer reviewers of journal articles should be doing, I rather wish to offer some account of what they should not be doing in order for scholarship to remain intact and knowledge production or educational research to retain authentic levels of erudition and conceptual rigour. By reflecting on my role as editor of this journal for almost a decade, I draw on reviews by peers in an attempt to advance the argument for rigorous peer reviews that do not dismiss authors’ work as unworthy of consideration. Rather, I argue that rigorous peer reviews avoid humiliating others’ work and consider submitted journal articles as intellectual thought pieces that deserve serious consideration and that remain in becoming. Finally, I make a case for rigorous peer review in South African higher education as being as important as the article submissions themselves, to the extent that peer reviewers, certainly in higher education, cannot turn a blind eye to the transformative agenda of social justice education. Failing to do so would ignore the richness associated with responsible scholarship.